ANALISIS PROSES PENDAFTARAN CALON ANGGOTA DPRD KOTA SEMARANG PADA PEMILU TAHUN 2024 - Hastuti, Listiawati Dwi; Sudrajat, Rahmat; Sutono, Agus (Civis : Jurnal Ilmiah Ilmu Sosial dan Pendidikan, 2025)
This research is based on direct observation at the Semarang City KPU, which shows that there are many problems in the registration of candidates for DPRD members, including registration information that is less informative, the time requirements and nominations are considered limited, and many more problems that can be explained descriptively. The purpose of this research is to find out the registration process of candidates for members of the Semarang City Regional People's Representative Council in the 2024 general election. The type of research used is qualitative with descriptive methods. Data collection techniques include observation, interviews, and documentation. The results of this study are in accordance with the research indicators, which show that the Semarang City KPU carries out the registration process for candidates for the Semarang City DPRD according to the regulations and standards set by the KPU of the Republic of Indonesia with the help of the nomination information system (Silon). The Semarang City KPU has organised the General Election in Semarang City according to the principle of LUBER JURDIL by determining the implementation according to the objectives, regulations, and standards for organising the election in 2024. This can be seen from the implementation of elections that have implemented national, permanent, and independent characteristics.